2007
DOI: 10.1039/b704231k
|View full text |Cite
|
Sign up to set email alerts
|

Emerging host–guest chemistry of synthetic nanotubes

Abstract: Emerging host-guest chemistry of synthetic nanotubes is reviewed, including the preparation of their encapsulation complexes, guest dynamics, exchange and potential applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…It is also reflected form the data that the process of achieving the equilibrium depends upon the concentration of the guest molecule. A recent review article by Organo et al reported that, at a certain concentration of the guest molecules, depending upon their characteristics, they can undergo an S N 2 type exchange in the nanotubes [32,33]. During this process the template experiences a movement to an appreciable extent [33].…”
Section: Steady State Anisotropic Description About the Heterogeneitymentioning
confidence: 96%
See 2 more Smart Citations
“…It is also reflected form the data that the process of achieving the equilibrium depends upon the concentration of the guest molecule. A recent review article by Organo et al reported that, at a certain concentration of the guest molecules, depending upon their characteristics, they can undergo an S N 2 type exchange in the nanotubes [32,33]. During this process the template experiences a movement to an appreciable extent [33].…”
Section: Steady State Anisotropic Description About the Heterogeneitymentioning
confidence: 96%
“…The anisotropy in case of 2 lM guest concentration appears to drop down to some extent before rebuilding to acquire a value that is less than that for 1 lM but more than 3 lM at $6 mM CD concentration. We suspect the dynamic nature of the guest-host chemistry as the probable reason behind this behaviour [32,33].…”
Section: Steady State Anisotropic Description About the Heterogeneitymentioning
confidence: 97%
See 1 more Smart Citation
“…The host-guest, inclusion compounds and solvates of the latter case have been called as pseudopolymorphs (9,10). The study of inclusion compounds is one of the hot topics in chemical research (11)(12)(13)(14)(15)(16)(17)(18)(19) since it has applications in magnetism, gas storage devices, nonlinear optical materials, targeted drug delivery, etc. (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…He successfully applied supramolecular chemistry for the molecular recognition of gases, where he was among the pioneers. He was the first to successfully introduce calixarene-based materials, including solid-supported calixarenes [28] and calixarene nanotubes, [29][30][31][32][33] for the chemical fixation [34,35] of NO 2 =N 2 O 4 , a major component of NO x gases. These aggressive environmental pollutants were converted into stable nitrosonium complexes, which were utilized further for controlled NO þ release (so-called ''encapsulated nitrosation reagents'' [36,37] ) or direct NO-gas release.…”
mentioning
confidence: 99%